The economics of exchange rates - Sarno, Lucio (Cambridge University Press, 2002)
In the last few decades exchange rate economics has seen a number of developments, with substantial contributions to both the theory and empirics of exchange rate determination. Important developments in econometrics and the increasingly large availability of high-quality data have also been responsible for stimulating the large amount of empirical work on exchange rates in this period. Nonetheless, while our understanding of exchange rates has significantly improved, a number of challenges and open questions remain in the exchange rate debate, enhanced by events including the launch of the Euro and the large number of recent currency crises. This volume provides a selective coverage of the literature on exchange rates, focusing on developments from within the last fifteen years. Clear explanations of theories are offered, alongside an appraisal of the literature and suggestions for further research and analysis
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Foreign exchange rates; Wechselkurstheorie; Wechselkurs